2016
DOI: 10.18632/oncotarget.12292
|View full text |Cite
|
Sign up to set email alerts
|

NKp44 and NKp30 splice variant profiles in decidua and tumor tissues: a comparative viewpoint

Abstract: NKp44 and NKp30 splice variant profiles have been shown to promote diverse cellular functions. Moreover, microenvironment factors such as TGF-β, IL-15 and IL-18 are able to influence both NKp44 and NKp30 splice variant profiles, leading to cytokine-associated profiles. Placenta and cancerous tissues have many similarities; both are immunologically privileged sites and both share immune tolerance mechanisms to support tissue development. Therefore, we studied the profiles of NKp44 and NKp30 splice variants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Shemesh et al also found that NKp44-2 and NKp44-3 isoforms predominated in decidual tissue obtained from the majority of first trimester spontaneous abortions, while a NKp44-1-dominant (inhibitory) profile was found in dNK cells from most elective abortions or term deliveries (healthy pregnancies), which is consistent with the inhibitory function of dNK cells in the study by Siewiera et al (95). …”
Section: Splice Variants Of Ncrs Resulting In Distinct Receptor Isoformssupporting
confidence: 77%
See 2 more Smart Citations
“…Shemesh et al also found that NKp44-2 and NKp44-3 isoforms predominated in decidual tissue obtained from the majority of first trimester spontaneous abortions, while a NKp44-1-dominant (inhibitory) profile was found in dNK cells from most elective abortions or term deliveries (healthy pregnancies), which is consistent with the inhibitory function of dNK cells in the study by Siewiera et al (95). …”
Section: Splice Variants Of Ncrs Resulting In Distinct Receptor Isoformssupporting
confidence: 77%
“…Moreover, a subset of GIST patients with predominant expression of the NKp30c isoform and a distinct haplotype involving two SNPs in the ncr3 gene were found to be associated with particularly poor survival (94). For GI carcinomas and variety of other cancers, we observed that both cancerous and matched normal tissues manifested balanced NKp30c inhibitory and NKp30a/b activation profiles; yet, we found skewed NKp30 splice variant profiles in about 50% of a variety of tumor tissues compared to their matched normal tissues (95). …”
Section: Splice Variants Of Ncrs Resulting In Distinct Receptor Isoformsmentioning
confidence: 79%
See 1 more Smart Citation
“…1). NKp44 (NCR2) is a 44 kDa protein, consisting of a single extracellular V-type Ig (IgV) domain (44)(45)(46), followed by a long stalk region and a hydrophobic transmembrane domain. The latter contains a charged lysine residue that leads to association with DAP12 adaptor with ITAM (47) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…PCNA intracellular functional range is associated with DNA replication, DNA repair, cell cycle control, apoptosis, chromatin metabolism, and gene expression ( 17 19 ). PCNA expression is upregulated in cancer cells relative to healthy normal cells and can be used as a marker of cell proliferation and cancer virulence in many types of cancers ( 9 , 20 27 ). Therefore, PCNA is considered as a potential therapeutic target in anticancer therapy ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%